At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
You isolate one variable. Let's say that x will be that variable in the first equation:
x-y=1
+y +y
x=y+1
So now you have the equation for x. All you have to do is substitute it into the other:
x=y+1
(y+1)+y=3
Combine like terms and solve:
2y+1=3
-1 -1
2y=2
2y/2=2/2
y=1
Now that you have the value of one, substitute it into either of the equations to find x.
If you put it in the first:
x-1=1
+1 +1
x=2
If you put it into the other, you would get the same answer.
Therefore, y=1 and x=2
x-y=1
+y +y
x=y+1
So now you have the equation for x. All you have to do is substitute it into the other:
x=y+1
(y+1)+y=3
Combine like terms and solve:
2y+1=3
-1 -1
2y=2
2y/2=2/2
y=1
Now that you have the value of one, substitute it into either of the equations to find x.
If you put it in the first:
x-1=1
+1 +1
x=2
If you put it into the other, you would get the same answer.
Therefore, y=1 and x=2
x - y = 1
x + y = 3
________
2x = 4
__ _
2 2
x = 2
x + y = 3
2 + y = 3
-2 -2
________
y = 1
(x, y) = (2, 1)
x + y = 3
________
2x = 4
__ _
2 2
x = 2
x + y = 3
2 + y = 3
-2 -2
________
y = 1
(x, y) = (2, 1)
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.